Technological strategies implemented by livestock farmers specialized in goat breeding in the mountain region of San Juan, Mendoza and La Rioja provinces in Argentina - Guzman, Fernando Diego (2023)
The goat farming is of great relevance in the mountain ranges of San Juan, La Rioja and Mendoza Provinces in Argentina. Out of the three, Mendoza province has the highest number of goats in the country. This system of production is majorly managed by the family members making it an integral part of the Family Farming sector.. This type of production generates work in a pauperized sector and at such places that are distant from the urban centres where possibility of alternative occupations is scare or almost nil. The animal rearing activity focuses on primary production with little value addition, high seasonality, and informal and rudimentary marketing strategies. These activities primarily employ tacit knowledge acquired over the years by trial-and-error method. Transhumance, as a strategy for the use of the natural environment, reveals the existence of a thorough knowledge of the seasonal productivity of the grasslands of the mountain valleys. Research and extension organizations develop projects aimed at improving these production systems through the implementation of contemporary technologies. The objective of this paper is to identify the technological strategies implemented by the Family Farming sector specialized in goat breeding in the mountain region of the provinces of Mendoza, San Juan and La Rioja, with specific focus on their origin, specific problems they face, and strategic similarities and differences to propose recommendations for the research and extension organizations.